Heterosexual masculinities and the self-reflexive novel - Rossoni, Stefano (Comparative Literature and Culture, 2025)
Heterosexual Masculinities and the Self-Reflexive Novel examines how the narratives of four world-renowned authors, namely J. M. Coetzee, Milan Kundera, Philip Roth and Mario Vargas Llosa, offer a standpoint through which to address the inscription of heterosexual masculinity into Western literary legacy and the ways in which masculinity is re-fashioned in contemporary self-reflexive novels. Considering the interconnectedness of their narratives for the first time, the book explores unexamined patterns of dialogue among Coetzee, Kundera, Roth and Vargas Llosa while also contextualising their writing in the light of the European literary tradition inaugurated by Cervantes's Don Quixote and continued by Flaubert's Madame Bovary. Rather than building on conventional theoretical approaches to literary studies, Stefano Rossoni develops a fresh and engaging approach by looking at these two works not only as narrative texts but most importantly as theories of literature. In dialogue with critical contributions that examined men's emotional illiteracy and struggle to develop a language for self-reflection, the book argues that the narratives of Coetzee, Kundera, Roth and Vargas Llosa engage with the tradition of the self-reflexive novel and its ramifications to reflect on masculinity as a socio-cultural construction. Ultimately, their writing reveals men's novelistic self-reflexivity as a site of unintelligibility